Assessment of malreduction standards for the syndesmosis in bilateral CT scans of uninjured ankles. (1st January 2021) - Kubik, Jeremy F.; Rollick, Natalie C.; Bear, Jessica; Diamond, Owen; Nguyen, Joseph T.; Kleeblad, Laura J.; Wellman, David S.; Helfet, David L.
Abstract : Aims: Malreduction of the syndesmosis has been reported in up to 52% of patients after fixation of ankle fractures. Multiple radiological parameters are used to define malreduction; there has been limited investigation of the accuracy of these measurements in differentiating malreduction from inherent anatomical asymmetry. The purpose of this study was to identify the prevalence of positive malreduction standards within the syndesmosis of native, uninjured ankles. Methods: Three observers reviewed 213 bilateral lower limb CT scans of uninjured ankles. Multiple measurements were recorded on the axial CT 1 cm above the plafond: anterior syndesmotic distance; posterior syndesmotic distance; central syndesmotic distance; fibular rotation; and sagittal fibular translation. Previously studied malreduction standards were evaluated on bilateral CT, including differences in: anterior, central and posterior syndesmotic distance; mean syndesmotic distance; fibular rotation; sagittal translational distance; and syndesmotic area. Unilateral CT was used to compare the anterior to posterior syndesmotic distances. Results: A difference of anterior to posterior syndesmotic distance > 2 mm was observed in 89% of ankles (n = 190) on unilateral CT assessment. Using bilateral CT, we found that 35% (n = 75) of normal ankles would be considered malreduced by current malreduction parameters. In 50 patients (23%), only one parameter was anomalous, 18 patients (8%) had two positive parameters and seven patients (3%) had three. Difference in fibular rotation had the lowest false positive rate of all parameters at 6%, whereas posterior syndesmotic distance difference had the highest at 15%. Conclusion: In this study, 35% of native, uninjured syndesmoses (n = 75) would be classified as malreduced by current diagnostic standards on bilateral CT and 89% had an asymmetric incisura on unilateral CT (n = 190). Current radiological parameters are insufficient to differentiate mild inherent anatomical asymmetry from malreduction of the syndesmosis. Cite this article: Bone Joint J 2021;103-B(1):178–183.